Repair of composites: Effect of laser and different surface treatments. (June 2015) - Barcellos, Daphne C.; Miyazaki Santos, Vivian M.; Niu, Li-Na; Pashley, David H.; Tay, Franklin R.; Pucci, Cesar R.
Abstract: Objectives: This study investigated the repairs of resin composite restorations after using different surface treatments. Design: Eighty four truncated cones of Filtek Z350 were prepared and thermo-cycled (20, 000 cycles). Surfaces were roughened with diamond bur and etched with 37% phosphoric acid. Those cones were divided into 7 groups ( N =12): 1) Prime&Bond 2.1; 2) aluminum oxide sandblasting+Prime&Bond 2.1; 3) Er:YAG laser treatment+Prime&Bond 2.1; 4) 9.6% hydrofluoric acid for 2 min+silane coupling agent.; 5) silane coupling agent; 6) auto-polymerized acrylic monomer+Prime&Bond 2.1; 7) Adper Scothbond SE. Teflon device was used to fabricate inverted truncated cones of repair composite over the surface-treated. The bonded specimens were stressed to failure under tension. The data were analyzed with one-way ANOVA and Tukey tests. Results: Mean repair strengths (SD, in MPa) were, Group-2: 18.8a; Group-1: 18.7a; Group-6: 13.4ab; Group-7: 9.5bc; Group-3: 7.5bcd; Group-4: 5.2cd; Group-5: 2.6d. Conclusions: The use of diamond bur and a conventional adhesive and the use of aluminum oxide sandblasting prior to adhesive provided a simple and cost-effective solutions to composite repair. Er:YAG laser, silane alone, 9.6% hydrofluoric acid plus silane or a self-etching adhesive results in inferior composite repair strengths. Clinical relevance: Diamond bur roughening alone or in combination with aluminum oxide sandblasting is equally effective in preparing a roughened surface for resin composite repair using Prime&Bond 2.1 as the adhesive.